Influence of Al-Si coating on microstructure and mechanical properties of fiber laser welded 22MnB5 steel. (August 2019) - Sun, Yiming; Wu, Laijun; Tan, Caiwang; Zhou, Wenlu; Chen, Bo; Song, Xiaoguo; Zhao, Hongyun; Feng, Jicai
Highlights: Al-Si coating affects the microstructure of 22MnB5 steel fiber laser welded joints. In fatigue test, strain localization occurs at the martensite/martensite interfaces. Coated welded joints performs lower anti-deformation capacity during Erichsen tests. Abstract: Fiber laser welding of as-received 22MnB5 steel with Al-10wt.%Si coating in butt configuration was performed. The influence of Al-Si coating on microstructure transformation and mechanical properties including tensile tests, fatigue tests and Erichsen cupping tests was investigated. Ferrite with Al enrichment (1.37 wt%) was found in the fusion zone (FZ) of coated welded joints with 15% area proportion, while nearly entire martensite structure composed the FZ in the case of de-coated joint. The strain localization was more likely to accumulate at the martensite/martensite interface rather than the ferrite/martensite interface due to the higher kernel average misorientation (KAM) values. Microhardness of the FZ in coated welded joints dropped by 50HV compared with that of de-coated welded joints. However, tensile properties were not affected since failure occurred at base metal (BM). Fatigue samples of coated welded joints showed better performance than the de-coated ones, suggesting that the ferrite in the FZ had positive effect on fatigue lives under cycling load conditions. The Erichsen cupping tests showed similar Erichsen values (5.60 mm and 5.67 mm) for de-coated and coated welded joints. An opposite effect of ferrite on Erichsen cupping tests was obtained. The peak force required for deformation dropped by 35% with Al-10wt.%Si coating.